Implementation of the Murabahah Agreement in Sharia Financial Institutions and a Review of Its Alleged Irregularities - Moh. Habibun Nawafil; Fajar Fajar; Khoirun Nasik; Aliya Riza Adiba (Yayasan Rahmat Islamiyah, 2026)
Murabahah contact is one of the most dominant products used in Islamic financial institutions because it is considered to have a relatively low level of risk and provides certainty of profit for financial institutions. However, the practice of murabahah in Islamic financial institutions often gives rise to various debates. Some parties consider the practice to be similar to the credit system in conventional banking. In addition, there are differences of opinion among scholars regarding the validity of several murabahah mechanisms, including the possibility of legal engineering.This study aims to analyze the concept of the murabahah contract from the perspective of fiqh muamalah using a library research method with a descriptive qualitative approach through the review of various literature sources such as the Qur'an, hadith, fatwas of DSN-MUI, laws and regulations, and other relevant scientific works.The results of the study indicate that murabahah is a valid sale and purchase contract under Islamic law as long as it fulfills the pillars and conditions, such as clarity of the cost price, agreement on the profit margin, and ownership of the goods by the seller before the contract is concluded. This research provides an academic perspective that can be used to evaluate and improve murabahah financing practices so that they are more in line with sharia principles.